(untitled) (Práxis Educativa, 2025)
This study analyzes the contributions of Zygmunt Bauman and Critical Theory to understanding and addressing the contemporary challenges of education in liquid modernity, with an emphasis on the Brazilian context. It starts from the problem of how to rethink education in the face of social fluidity and neoliberal rationality, examining the relationship between ethics, solidarity, and emancipation. The research adopts a hermeneutic epistemology inspired by Bauman’s interpretive sociology, employing a qualitative approach and literature review. The dialogue with Adorno, Horkheimer, Habermas, and Bauman shows that education, often subjected to technocratic and market logics, can constitute a critical and reflective space oriented toward responsibility and social justice. The results indicate the need to reassert the ethical role of schools and educators in building democratic and solidarity-based relationships. Keywords: Liquid modernity. Critical Theory. Education and ethics.